Tapered, Double-Lead Threads Single Implants Placed in Fresh Extraction Sockets and Healed Sites of the Posterior Jaws: A Multicenter Randomized Controlled Trial with 1 to 3 Years of Follow-Up. (13th September 2017) - Cucchi, Alessandro; Vignudelli, Elisabetta; Franco, Simonetta; Levrini, Luca; Castellani, Dario; Pagliani, Luca; Rea, Massimiliano; Modena, Claudio; Sandri, Giulio; Longhi, Carlo
Abstract : Purpose . To evaluate the survival, success, and complication rates of tapered double-lead threads single implants, placed in fresh extraction sockets and healed sites of the posterior jaws. Methods . The enrolled patients were randomly divided into 2 groups: in the test group (TG), all implants were inserted at the time of tooth extraction; in the control group (CG), all implants were placed 3 months after extraction. The implants were followed for a period of 1 to 3 years after loading. The main outcomes were implant survival, complications, and implant-crown success. Results . Ninety-two patients had 97 installed implants (49 in the TG, 48 in the CG). Only two implants failed, in the TG; the survival rates were therefore 95.9% (47/49) and 100% (48/48) for TG and CG, respectively. In the surviving implants, no complications were reported, for an implant-crown success of 100%. Conclusions . Although a significant difference was found in the levels of primary stability between TG and CG, single implants placed in fresh extraction sockets and healed sites of the posterior jaws had similar survival and complication rates. Crestal bone levels and peri-implant bone resorption showed similar values. A longer follow-up period is however required, to confirm these positive outcomes.